Validation of a new equinometer device for measuring ankle range of motion in patients with cerebral palsy: An observational study - Horsch, Axel; Kleiber, Saskia; Ghandour, Maher; Klotz, Matthias C. M.; Hetto, Pit; Tsitlakidis, Stefanos; Alimusaj, Merkur; Götze, Marco (Medicine, 2022)
The goniometer is the gold-standard measurement tool of ankle range of motion (ROM). However, several studies have questioned its inter- and intra-rater reliability. Therefore, we conducted this validation study to assess the reliability of a different tool, named Equinometer, as a measurement device of ankle ROM in addition to comparing the reproducibility of their results. - Sixteen healthy individuals were included. They underwent both goniometer and Equinometer measurements in knee extension and 90° knee flexion (Silfverskjöld Test). Three raters reported the values of dorsiflexion (DF) and plantarflexion (PF) in each session using both measurement tools. Intra-rater reliability was assessed between 2 raters on another study group of 24 participants. Intraclass correlation coefficients were used to determine the reliability of the used device. - The age of study subjects ranged from 22 to 85 years. Fifty percent were males, and the right ankle joint was the most examined side (68.75%). In terms of DF and PF during knee extension and flexion, our analysis revealed that the measurements recorded by the Equinometer were equivalent to the goniometer. Of note, the intra-rater reliability of the Equinometer was excellent for both DF and PF assessment during both knee flexion and extension (Intraclass correlation coefficient ranged from 0.90 to 0.98), with minimal mean differences from goniometer measurements. Subgroup analysis based on age did not reveal any significant differences (P > .05). - Given the high intra-rater correlations of the Equinometer, we suggest that it is reliable and precise in recording ankle ROM in outpatient clinics, particularly to obtain reproductive, comparable and unbiased data from different observers.
Gesehen am 29.06.2022